Medical therapy doses at hospital discharge in patients with existing and de novo heart failure. (20th June 2019) - Diamant, Michael J.; Virani, Sean A.; MacKenzie, Winston J.; Ignaszewski, Andrew; Toma, Mustafa; Hawkins, Nathaniel M.
Abstract: Aims: Uptitrating angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers (ACE‐I/ARBs), beta‐blockers, and mineralocorticoid receptor antagonists (MRAs) to optimal doses in heart failure with reduced ejection fraction (HFrEF) is associated with improved outcomes and recommended in guidelines. Studies of ambulatory patients found that a minority are prescribed optimal doses. However, dose at hospital discharge has rarely been reported. This information may guide quality improvement initiatives during and following discharge. Methods and results: We assessed 370 consecutive patients with HFrEF hospitalized at two centres in Vancouver, Canada. Of those without contraindications, 86.4%, 93.4%, and 44.7% were prescribed an ACE‐I/ARB/sacubitril–valsartan, beta‐blocker, or MRA, respectively. The proportion of eligible patients prescribed target dose was respectively 28.6%, 31.7%, and 4.1%. Forty‐two of 248 eligible patients (16.9%) were prescribed ≥50% of target dose, and only three patients received target dosing of all three medication classes. In multivariate regression models, cardiologist involvement in care was independently associated with increased dose and prescription of ≥50% of target dose for all medications, whereas a history of HF was only predictive for beta‐blockers. Conclusions: In a single‐region experience of hospitalized HFrEF patients, a high proportion of eligible patients were discharged on ACE‐I/ARB or beta‐blocker. Less than half were prescribed MRAs, and few were prescribed ≥50% or target dosing of all medications. Further exploration into barriers to medication uptitration, and improvement in processes of care, is needed.